SEJARAH PERKEMBANGAN PEREMPUAN INTELEKTUAL DI IAIN SUNAN AMPEL SURABAYA 1971-2014 - Rega Iqbal Ghany (Qurthuba: The Journal of History and Islamic Civilization, 2020)
Abstract: This article examines women's intellectuals, especially among female students at IAIN Sunan Ampel Surabaya. Researchers provide limitations on three things, namely: (1). What is the Profile of IAIN Sunan Ampel Surabaya (2). How are the dynamics of the role and position of intellectual women in the internal campus of IAIN Sunan Ampel (3). What are the Roles of Intellectual Women at IAIN Sunan Ampel in Society. This article was prepared using historical research methods, namely: heuristics, verification, interpretation and historiography. The approach used is a historical approach from a diachronic perspective. In addition, the authors also use a descriptive qualitative approach. While the theory used is the theory of Continuity and Change (the theory of continuity and change) and the theory of Role (role theory). From the results of the research conducted, it can be concluded that: (1). IAIN Sunan Ampel was officially established in 1965 with the Decree of the Minister of Religion Number 20/1965 based in Surabaya. In the period between 1966-1970, IAIN Sunan Ampel had 18 (eighteen) faculties spread across 3 (three) provinces. (2). Women in the internal institutions of IAIN Sunan Ampel from their female students show a development of awareness of the importance of education. (3). Not only on the internal campus but also plays a lot of roles on the external campus in various fields. Keywords: history, woman, intellectual, IAIN